Marketing Efficiency of Rajangan Tobacco in Suntalangu Village, East Lombok Regency - Masrun, Masrun; Ilhamudin, M. (Jurnal Multidisiplin Sahombu, 2025)
Suntalangu village is one of the villages with natural potential that greatly supports its community in improving the economy through the agricultural sector on tobacco plants. This study aims to determine the margin and efficiency of tobacco marketing in Suntalangu village. The analysis used is qualitative descriptive for marketing channels and quantitative on revenue, margin and marketing efficiency (Farmer's Share). The data collection method was carried out with survey samples of farmers/tobacco producers, village collectors/middlemen, wholesalers, e-traders, and end consumers. The results of this study show that there are 4 marketing channels for tobacco marketing in Suntalangu village, East Lombok regency. In pattern I, there are producers, village collectors (middlemen), wholesalers, retailers, and end consumers. Pattern II includes producers, village collectors (middlemen), retail traders, and end consumers. Pattern III consists of producers, village collectors (middlemen), and end consumers. IV pattern from producer to end consumer. The most efficient marketing channel according to the three indicators from the farmer's side is the marketing channel III because the marketing margin is smaller, the Farmer's Share and the value of the profit to marketing cost ratio is the highest compared to other marketing channels. To create efficient tobacco marketing in the long term, it is recommended that farmers participate in partnership activities, because partnerships absorb a lot of tobacco, smooth input and output and can reduce transaction costs. For this reason, the government can facilitate partnership activities, in order to facilitate the partnership process.